Postpneumonectomy oesophagopleural fistula. - Van Den Bosch, J M (1980)
Patients with oesophagopleural fistula after a pneumonectomy present a difficult therapeutic problem. There are two types of presentation, early and late. We report three cases in addition to the 49 previously published. All three patients developed their fistulae after right-sided pneumonectomy (one month, four years, and 21 years respectively) and presented with the features of an empyema. The existence of an oesophagopleural fistula can be demonstrated by the discovery of food particles in the pleural aspirate, by direct visualisation during oesophagoscopy after instilling methylene blue into the pleural cavity, by barium swallow, or by identification of helium in the pleural space after swallowing a mouthful of helium. After the initial treatment of empyema we believe that surgical repair of the oesophagopleural fistula is the treatment of choice.